Synchrony in serum antibody response to conserved proteins of Moraxella catarrhalis in young children. Issue 12 (1st December 2020) - Ren, Dabin; Bajorski, Peter; Murphy, Timothy F.; Lafontaine, Eric R.; Pichichero, Michael E.
ABSTRACT: Conserved Moraxella catarrhalis ( Mcat ) proteins, oligopeptide permease (Opp)A, hemagglutinin (Hag), outer membrane protein (OMP) CD, Pilin A clade 2 (PilA2), and Moraxella surface protein (Msp) 22 have been studied as vaccine candidates. Children who experience frequent acute otitis media (AOM) confirmed with pathogen identification by tympanocentesis are referred to as stringently-defined otitis prone (sOP). Synchrony of serum antibody responses against 5 Mcat proteins, OppA, Hag, OMP CD, PilA2, and Msp22 resulting from nasopharyngeal colonization and AOM was studied for 85 non-otitis prone (NOP) children and 34 sOP children. Changes in serum IgG were quantitated with ELISA. Serum IgG antibody levels against OppA, Hag, OMP CD, and Msp22 rose in synchrony in NOP and sOP children; that is, the proteins appeared equally and highly immunogenic in children at age 6 to 22–25 months old and then leveled off in their rise at 22–25 to 30 months old. In contrast, rises of PilA2 were slow from 6 months old and kept constant and did not level off significantly before 30 months old. OppA, Hag, OMP CD, and Msp22 elicited a synchronous acquisition of naturally-induced serum antibody in young children. A multi-valent Mcat protein vaccine combining OppA, Hag, OMP CD, and Msp22 may exhibit less antigen competition when administered as a combination vaccine in young children.